COMPETITION OF JAVANESE AND INDONESIAN: A MIXED-METHODS APPROACH TO YOUNG MULTILINGUALS’ LANGUAGE CHOICE - Erna Andriyanti; Mehdi Riazi (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2020)
Multilingualism differs from place to place, with different pressures and outcomes depending on each unique situation. In Indonesian context, an important factor is the status and over prestige afforded to the national language, posing a possible threat to local language vitality. This study reports the position of Javanese and Indonesian as parts of the language repertoire of young Yogyakartan multilinguals in three domains: home, school, and the street. A mixed-methods approach was used and the main data were collected through questionnaire and observations at ten participating high schools. The students’ survey was responded by 1,039 students. Their natural language use was recorded at school playground. Supporting data were collected from language teachers’ survey and interviews with school authorities. The findings show that Javanese and Indonesian still compete in the three domains but not in all sociolinguistic situations. The youths’ Javanese-Indonesian choice is mostly dependent on gender and parental level of education.Keywords: multilinguals, language domains, language choice, sociolinguistic study KOMPETISI BAHASA JAWA DAN BAHASA INDONESIA:PENDEKATAN MIXED-METHODS TERHADAPPILIHAN BAHASA ANAK MUDA MULTILINGUAL AbstrakMultilingualisme berbeda di satu tempat dari tempat lainnya, dengan penekanan dan hasil tergantung pada masing-masing situasi yang khas. Di dalam konteks Indonesia, faktor yang penting adalah status dan prestis yang disematkan untuk bahasa nasional, yang bisa mengancam vitalitas bahasa-bahasa daerah. Artikel ini mengkaji posisi bahasa Jawa dan bahasa Indonesia sebagai bagian dari repertoar bahasa anak muda multilingual di Yogyakarta dengan fokus pada tiga domain: rumah, sekolah, dan jalan. Pendekatan mixed-methods digunakan dan data utama dikumpulkan melalui kuesioner and observasi di sepuluh sekolah menengah. Survei terhadap siswa melibatkan 1.039 responden dan perekaman percakapan natural siswa dilakukan di saat jam istirahat. Data penunjang bersumber pada survei guru dan wawancara dengan pihak otoritas sekolah. Hasil penelitian menunjukkan bahwa penggunaan bahasa Jawa dan bahasa Indonesia masih berimbang di ketiga domain tetapi tidak pada semua situasi sosiolinguistik. Pilihan bahasa oleh responden sebagian besar berkorelasi positif terhadap gender dan tingkat pendidikan orang tua. Keywords: multilingual, domain bahasa, pilihan bahasa, kajian sosiolinguistik